Productive capacity and genetic variation behavior in progenies from irrigated açai according to plant age - João Tomé de Farias Neto; Gilberto Ken Iti Yokomizo; Marcos Deon Vilela de Resende (Agro@mbiente On-line)
The açai fruit yield is concentrated between the months of July to December (harvest), providing an important income to actors involved in the production chain, however in the off-season this brings serious socioeconomic problems, with the need for research that may offer selected genetic materials that can circumvent this problem. However, the age for making this selection in this species is unknown. Therefore, the objective of this work was to infer the best age for selection by estimating genetic and phenotypic parameters in the different stages of evaluating progenies of half-sibs of acai. The experiment followed a randomized block design with three replications and five plants per plot, with 30 progenies. The statistical analysis was performed using the REML/BLUP methodology. The results showed that the magnitudes of the estimates of heritability and genetic variation decrease with age; the correlations between the characters that make up fruit yield reveal that the number of bunches is the most important component of yield; for the fruit yield character, the age of progenies and harvest years indicate that early selections are more efficient; the early emission of tillers is an important characteristic to be sought in açai breeding programs guaranteeing greater fruit yield in adult plants; and higher fruit yield in the off-season is possible from the fourth year of harvest.